Antidiarrheal Activity of Ethanolic Extract of Vernonia amygdalina Del Leaves againts Male Mice Induced by Oleum Ricini - Karunita Ika Astuti; Lusiana Dwi Wulandari; Eka Fitri Susiani (Borneo Journal of Pharmacy, 2019)
Leaves of Vernonia amygdalina Del. is one of the alternative plants that people use as antidiarrheal in Martapura, Banjar. The purpose of research to determine the antidiarrheal activity and the effectiveness of ethanolic extract of leaves against male mice. The negative control was given NaCMC 0.5% orally, positive control was given Loperamide HCl 0.005 mg/20 g orally, and groups of ethanolic extract of leaves were given dosages in 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW orally. After 1 hour of treatment, the groups were induced by Oleum ricini orally and were observed for 4 hours. Based on three parameters were frequency, weight, and consistency of diarrhea. From the results observation of that negative control, positive control, EEDA 100 mg/kg BW, 200 mg/kg BW, and 400 mg/kg BW for diarrhea frequency parameter was 7.4 ± 2.30; 2 ± 1.22; 5.8 ± 3.34; 6.2 ± 4.08; 2.4 ± 1.67; the weight parameter was 1.34 ± 0.43; 0.38 ± 0.29;0.66 ± 0.56; 0.57 ± 0.38; 0.49 ± 0.33 and then consistency of diarrhea with EEDA 400 mg/kg BW improved the consistency at 180 minutes compared to control group at 210 minutes. In conclusion, from all parameters of ethanolic extract of Vernonia amygdalina Del. leaves can give an antidiarrhea effect with optimum dosage is 400 mg/kg BW.